ANALISIS RISIKO DAN FAKTOR PENYEBAB TABRAKAN KAPAL KM. ARMADA SEJATI DI PELABUHAN SURABAYA DALAM KAITANNYA HUKUM MARITIM - susiani, dina (Journal of Law and Administrative Science, 2023)
Abstract; This research aims to find out about the risk of danger from ship collisions and to find out the factors that influence the risk of KM ship collisions. True Fleet at PT. Greetings Pacific Indonesia Lines. The type of research in this research is Normative Juridical research. The research approaches in this research are the statutory approach and the case approach. Sources of legal materials in this research are primary legal materials, secondary legal materials and tertiary legal materials. Data collection in this research used library research. Analysis will also be carried out using qualitative methods. The research results show that risk identification mapping of hazards that occur in activities on Armada Sejati ships can be carried out using the HAZOP or hazard method and the results show that the most dominant hazards are risks identified from several hazard sources such as ship accidents, painting, welding, mooring/unmooring, to loading and unloading goods. The occurrence of ship collision accidents can be caused by several factors, namely technical factors related to monitoring the ship's seaworthiness, natural factors related to weather and currents, human factors related to the human resources of the crew and also the company, as well as other factors.